O campesinato no sudoeste paulista: antropologia ambiental como subsídio à extensão universitária no Campus Lagoa do Sino da UFSCar - Santi, Tiago (Universidade Federal de São Carlos, 2020)
Known as the “hunger branch” and distinguished by its family farmers, the Southwest of São Paulo state is one of the least developed regions of the state. As part of a long history of poverty and social inequalities, the implantation of the Lagoa do Sino Campus of the Federal University of São Carlos in 2014 has represented an opportunity for the development of the region, being university extension among family farmers one of its pillars. Based on environmental anthropology and aiming to contribute to extensionism in the region, this dissertation brings out elements of productive history, practices, and traditional knowledge of its family farmers. Nine rural families from the municipalities of Angatuba, Buri and Campina do Monte Alegre have participated in this research. The fieldwork was carried out between October 2019 and January 2020, with a total of 27 visits to the properties and 22 people interviewed. The results bring to the light socioeconomic aspects of the region, the transformations in the local landscape, the productive strategies in the past and the present, as well as the traditional practices and knowledge among family farmers. The regional history of poverty and environmental degradation is related to a process of economic development that has always privileged the land property over the small producer. A pendular movement between diversification (1950-1980) and specialization (1980-2019) of productive strategies was also observed, which may shed light on the future of family farming in the region. It was also possible to show that traditional knowledge remains with some degree of complexity, playing a role in the productive strategies and decision-making of families. Its incorporation into extension projects may be one of the keys to the promotion of agriculture in the region as based on social justice, cultural valorization and environmental responsibility.
The peasantry in the Southwest of São Paulo state: environmental anthropology as a subsidy for university extension at the Lagoa do Sino campus of the UFSCar
Keywords: Campesinato; Agricultura familiar; Extensão universitária; Antropologia ambiental; Peasantry; Family farming; University extension; Environmental anthropology; CIENCIAS HUMANAS::ANTROPOLOGIA::ANTROPOLOGIA RURAL; CIENCIAS SOCIAIS APLICADAS; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL